Closed incision management with VAC Prevena after lower-limb surgery: literature review and local experience. Issue 2 (2018) - Luke, Hsien Tsung Tay; Yap, Hao Yun; Shaun, Qing Wei Lee; Chng, Siew Ping; Chong, Tze Tec; Tang, Tjun Yip
No abstract available